Update on Topical Corticosteroids: Classification, Clinical Use, and Adverse Effects [Actualización Terapéutica en Corticoesteroides Tópicos: Clasificación, Usos Clínicos y Efectos Colaterales] - Aedo-Inostroza, G (Ediciones Doyma, S.L., 2023)
[No abstract available]